Possible involvement of superoxide and dioxygen with cryptochrome in avian magnetoreception: Origin of Zeeman resonances observed by in vivo EPR spectroscopy - Hogben, H; Efimova, O; Wagner-Rundell, N; Timmel, C; Hore, P (2009)
The radical pair model of the avian magnetic compass centres around magnetically sensitive chemical reactions in the retina. Recent studies of migratory birds subjected to oscillating magnetic fields found remarkably sensitive disorientation responses when the frequency of the applied field (∼1.3 MHz) matched the EPR condition of a radical with g ≈ 2 in the Earth's magnetic field (∼47 μT). The occurrence of such 'Zeeman resonances' can be understood if one of the radical pair partners is devoid of hyperfine interactions. Here we examine the possibility that this radical is either superoxide or dioxygen and conclude that neither offers a very credible explanation for these in vivo EPR 'signals'. © 2009 Elsevier B.V. All rights reserved.